Stem Cells a better way for Treatment: Diabetes - Kumari, Mamta; Pandey, Parmanand; Sachan, Anupam Kr (Asian Journal of Pharmaceutical Research and Development, 2021)
Insulin-producing cells derived from the stem cell embryonic stem cell and pluripotent stem cell have been long duration to encourage, but evasive treatment far from clinical interpret into type1 diabetes therapy. Although stem cell therapies provide a great opportune time there is also conceivable risk such as teratoma formation to relate with the treatment. Mesenchyme stem stromal cells have due to their modulator effects on immunity, inflammation, and tissue repair been suggested to be used to either halt beta-cell loss during T1D development or be used to protect and support pancreatic islets when transplanted. This review aims to give an overview of the current knowledge of stem cell therapy outcomes in animal models of type-1diabetes and a proposed road map towards the clinical setting with a special focus on the potential risks and hurdles which need to be considered. From a clinical point of view, transplantation of insulin-producing cells derived from stem cells must be performed without immune suppression to be an attractive treatment option.